Monitoring Arctic permafrost: examining the contribution of volunteered geographic information to mapping ice-wedge polygons - Walz, Pauline; Fritz, Oliver; Marx, Sabrina; Mueller, Marlin M.; Thiel, Christian; Lenz, Josefine; Kaiser, Soraya; Frappier, Roxanne; Zipf, Alexander; Langer, Moritz (The Cryosphere, 2025)
This study evaluates the potential of Volunteered Geographic Information (VGI) for mapping and monitoring ice-wedge polygons in Arctic permafrost regions through two case studies in Alaska and Canada. We developed and tested a web-based mapping application that enables volunteers to identify ice-wedge polygon centroids in high-resolution aerial imagery, with data collected from 105 contributors as part of organized mapping events. The volunteer-contributed data achieved completeness scores of 88.74 % and 70.81 % for the Cape Blossom (Alaska) and Blueberry Hills (Canada) study regions respectively, with median positional accuracies of 1.29 and 1.38 m (both validated against expert mapping data). Analysis shows that contributions from approximately five volunteers per polygon are sufficient to achieve reliable results. Using Voronoi diagrams derived from the crowd-sourced centroids, we successfully reconstructed ice-wedge polygon networks and extracted key geomorphological and hydrological parameters including polygon area, perimeter, and network topology. The results demonstrate that VGI can effectively support permafrost monitoring by enabling efficient mapping of ice-wedge polygons across large areas while maintaining high data quality standards.